Membrane Topology Mapping of the O-Antigen Flippase (Wzx), Polymerase (Wzy), and Ligase (WaaL) from Pseudomonas aeruginosa PAO1 Reveals Novel Domain Architectures - Salim T. Islam (American Society for Microbiology, 2010)
ABSTRACT Biosynthesis of B-band lipopolysaccharide (LPS) in Pseudomonas aeruginosa follows the Wzy-dependent pathway, requiring the integral inner membrane proteins Wzx (O-antigen [O-Ag] flippase), Wzy (O-Ag polymerase), and WaaL (O-Ag ligase). For an important first step in deciphering the mechanisms of LPS assembly, we set out to map the membrane topology of these proteins. Random and targeted 3′ wzx, wzy, and waaL truncations were fused to a phoA-lacZα dual reporter capable of displaying both alkaline phosphatase and β-galactosidase activity. The results from truncation fusion expression and the corresponding differential enzyme activity ratios allowed for the assignment of specific regions of the proteins to cytoplasmic, transmembrane (TM), or periplasmic loci. Protein orientation in the inner membrane was confirmed via C-terminal fusion to green fluorescent protein. Our data revealed unique TM domain properties in these proteins, particularly for Wzx, indicating the potential for a charged pore. Novel periplasmic and cytoplasmic loop domains were also uncovered, with the latter in Wzy and WaaL revealing tracts consistent with potential Walker A/B motifs. IMPORTANCE The opportunistic pathogen Pseudomonas aeruginosa synthesizes its virulence factor lipopolysaccharide via the Wzy-dependent pathway, requiring translocation, polymerization, and ligation of lipid-linked polysaccharide repeat units by the integral inner membrane proteins Wzx, Wzy, and WaaL, respectively. However, structural evidence to help explain the function of these proteins is lacking. Since membrane proteins are difficult to crystallize, topological mapping is an important first step in identifying exposed and membrane-embedded domains. We mapped the topologies of Wzx, Wzy, and WaaL from P. aeruginosa PAO1 by use of truncation libraries of a randomly fused C-terminal reporter capable of different enzyme activities in the periplasm and cytoplasm. Topology maps were created based directly on residue localization data, eliminating the bias associated with reliance on multiple topology prediction algorithms for initial generation of consensus transmembrane domain localizations. Consequently, we have identified novel periplasmic, cytoplasmic, and transmembrane domain properties that would help to explain the proposed functions of Wzx, Wzy, and WaaL.